Ecophysiology of Adonis distorta, a high-mountain species endemic of the Central Apennines - Di Cecco, Valter; Catoni, Rosangela; Puglielli, Giacomo; Di Martino, Luciano; Frattaroli, Anna Rita; Gratani, Loretta (Lazaroa, 2016)
Morphological, anatomical and physiological plant and leaf traits of A. distorta, an endemic species of the Central Apennines on the Majella Massif, growing at 2,675 m a.s.l, were analyzed. The length of the phenological cycle starts immediately after the snowmelt at the end of May, lasting 128 ± 10 days. The low A. distorta height (Hmax= 64 ± 4 mm) and total leaf area (TLA= 38 ± 9 cm2) associated to a high leaf mass area (LMA =11.8±0.6 mg cm−2) and a relatively high leaf tissue density (LTD = 124.6±14.3 mg cm−3) seem to be adaptive traits to the stress factors of the environment where it grows. From a physiological point of view, the high A. distorta photosynthetic rates (PN =19.6 ± 2.3 µmol m−2 s−1) and total chlorophyll content (Chla+b = 0.88 ± 0.13 mg g−1) in July are justified by the favorable temperature. PN decreases by 87% in September at the beginning of plant senescence. Photosynthesis and leaf respiration (RD) variations allow A. distorta to maintain a positive carbon balance during the growing season becoming indicative of the efficiency of plant carbon use. The results could be an important tool for conservation programmes of the A. distorta wild populations.